Orientation of Rohida Defoliator, Patialus tecomella (Coleoptera: Curculionidae) to Different Light Colours and Varieties of Tecomella undulata (Sm.) Seem - Sharma, Meeta; Ahmed, S. I. (Indian Forester, 2004)
Tecomella undulata (Sm.) Seem, commonly known, as 'Marwar teak' is an important agroforestry tree species of arid and semi-arid region. The distribution pattern of T. undulata in desert area of India is quite obvious because of its sparking features of drought tolerant, high quality of timber, fuel wood and fodder etc.T. undulata is frequently severely attacked by a curculionid pest, patialus tecomella. In the present paper an attempt has been made to study the orientation of adult weevils to different colour. Besides, the tactic response of the weevils towards two varieties of T. undulata is also studied as the knowledge of feeding preference may lead towards possible means of reducing damage level in the field. There was a significant difference in the attraction of weevils towards different colours when tested simultaneously. White colour attracted the maximum number of weevils (64.66 ♂ and 51.32 ♀) that was highly significant over the three other colours tested. Yellow colour was the second to attract both the sexes as being 21.32% males and 29.32% females respectively. Minimum numbers of weevils were attracted towards blue and green colours when tested simultaneously (10 ♂ 14 ♀ and 4 ♂ 5.32 ♀ respectively). The attraction of P. tecomella towards white colour was proved to be highly useful in evolving the effective devices for mechanical control. Out of both the host varieties (T. undulata var., yellow flower and T. undulata var., orange flower) that were offered to the adult weevils at threee different temperatures viz., 15°,25° and 35°C, yellow flower variety was the most preferred food source when compared to orange flower variety. Maximum feeding activity (37.80 mm2 ) has been recorded to occur at 35°C on orange flower variety of T. undulata.